Vibration and tipping of agricultural machinery: a reality to be adjusted - Moraes, Guilherme Aparecido Gomes de [UNESP]; Santos, João Eduardo Guarnetti dos [UNESP]; Andreoli, André Luiz [UNESP]; Cagnon, José Angelo [UNESP]; Meneghetti, Vinicius G. [UNESP] (Crc Press-taylor & Francis Group, 2014)
The present study aimed to develop a methodology for the collection, transfer, storage and processing of vibration levels emitted in jobs occupied in agricultural machinery. The reason of this work is the study the vibration dose applied to operators of heavy vehicles and its relation to occupational health, linking the still high number of accidents involving farm machinery in relation to overturning (tipping). There is a need for the development and improvement of efficient tools in measuring vibration and tilt machine work, which minimize damage to health and accident risks for operators. © 2014 Taylor & Francis Group, London, UK.